Letter (copy) : Spanish workers' children and Christmas - Tewson, Vincent
032-0183-001 International. HVT/WJBA/AT/287 6th December, 1938. Sr. F. Trabal, Departament d'Economia, Generalitat de Catalunya, Barcelona. Dear Sir, SPANISH WORKERS' CHILDREN AND CHRISTMAS With further reference to your letter of the 22nd November, we duly communicated with Comrade Schevenels and he has promised to consult with Comrade Santiago about the possibility of doing something special for the children of the Spanish workers during Christmas. He thinks, with us, that the idea is a most excellent one and he is of the opinion that if a plan can be arranged, all the children should come in it that are in the territory under the Spanish Republican Government. However, we are compelled to point out that so far as can be calculate the total cost of consigning, say, a small parcel for each child, would be extremely high and it is going to be extremely difficult to obtain the extra funds required: we have naturally been concentrating on getting as much foodstuff as possible transferred, seeing that this is so urgently required. As a matter of fact the largest consignment of foodstuff hitherto shipped will be going shortly from us to your country, in order that distribution can take place about Christmas time. Yours faithfully, Assistant Secretary. 292/946/32/183